Evaluation of spam detection and prevention frameworks for email and image spam - a state of art - Hayati, Pedram; Potdar, Vidyasagar (Association for Computing Machinery (ACM), 2008)
In recent years, online spam has become a major problem for the sustainability of the Internet. Excessive amounts of spam are not only reducing the quality of information available on the Internet but also creating concern amongst search engines and web users. This paper aims to analyse existing works in two different categories of spam domains - email spam and image spam to gain a deeper understanding of this problem. Future research directions are also presented in these spam domains.